Numerical investigation of the temperature field and thermal insulation design of cold-region tunnels considering airflow effect. (5th June 2021) - Lu, Taishan; Zhang, Guozhu; Liu, Songyu; Zheng, Bo; Zhang, Xiang
Highlights: A three-dimensional numerical model considering the airflow effect is developed. The factors affecting the temperature of the surrounding rock are evaluated. Thermal resistance is introduced to assess the performance of insulation layers. Abstract: Recently, an increasing number of tunnels have been constructed in cold regions, leading to an urgent necessity to analyse the temperature fields in these tunnels and design reasonable thermal insulation layers under ventilation. This investigation aimed to numerically obtain the actual temperature field of a cold-region tunnel and optimise the design of the thermal insulation layer considering the airflow effect. A three-dimensional numerical model of convection heat transfer was established. Model test results and field data were used to validate the numerical model. Four formulas were developed to consider the effects of airflow velocity, initial temperature, volumetric specific heat capacity, and thermal conductivity on the temperature of the surrounding rock. The results indicated that the temperature variation at the preliminary surface becomes stable in the 5th year after tunnel excavation. Meanwhile, the thermal conductivity of the surrounding rock is the most influential factor affecting the temperature of the primary lining surface, followed by the volumetric specific heat capacity, initial temperature, and airflow velocity. The initial temperature has the most pronounced effect on the temperature of the surrounding rock with a buried depth of 4 m. The effects of thermal conductivity and airflow velocity are minimal. Furthermore, the thermal resistance, rather than the thickness of the insulation layer, is recommended for assessing the freeze-proof performance. The thermal resistance of the insulation layer of a highway tunnel should be larger than 0.048 °C/W. The optimal ratio of the thermal conductivity to the thickness of the insulation layer was observed to be 1.49.